JOURNALIST PUBLIC WORK IN US UNIVERSITIES - Khrystyna Martsikhiv (Pavlo Tychyna Uman State Pedagogical University, 2018)
The article deals with the application of public activity method on the example of professional training of journalists in US universities. The implemen-tation of journalist public work into curricula has been characterized. The research provides factors that influence the successful integration of journalist public work in the learning process. The difficulties of student public work implementation in the learning process as well as positive results of this method application in practice have been analysed. It is defined that the method of public work promotes the development of leadership, personal and social qualities among journalist students. Based on constructivist paradigm the service-based and collaborative approaches in journalism studying have been analysed. The article also describes how service learning from the point of constructivist approach can facilitate inter-active method of journalist studying. The benefits of experiential learning in jour-nalist educational process have been outlined. Three domains of experiential lear-ning have been identified: cognitive or mental skills; affective or emotional areas; manual or physical skills. It is noted that each domain has series of categories that reflect the level and type of learning. It is stated that each category represents a hierarchy moving from passive learning to active and points out the role of experiences in journalist studying. The article highlights the modes which experiential learning is based on: receptive mode that consists of shooting video, recording speeches by journalists; analytical mode is focused on developing critical thinking of journalists; productive mode is concentrated on accomplishing difficult tasks and journalist adapting to challenging situations; development mode consists of acquiring competence and mastery in professional sphere; psychological mode deals with personal and social growth of journalists. The prospects of further research in this area have been revealed.